RAGE contributes to allergen driven severe neutrophilic airway inflammation via NLRP3 inflammasome activation in mice - Katherine N. Killian; Jessica L. Kosanovich; Madeline A. Lipp; Kerry M. Empey; Kerry M. Empey; Kerry M. Empey; Tim D. Oury; Timothy N. Perkins (Frontiers in Immunology, 2023)
BackgroundAsthma is a major public healthcare burden, affecting over 300 million people worldwide. While there has been great progress in the treatment of asthma, subsets of patients who present with airway neutrophilia, often have more severe disease, and tend to be resistant to conventional corticosteroid treatments. The receptor for advanced glycation endproducts (RAGE) plays a central role in the pathogenesis of eosinophilic asthma, however, it’s role in neutrophilic asthma remains largely uninvestigated.MethodsA mouse model of severe steroid resistant neutrophilic airway disease (SSRNAD) using the common fungal allergen Alternaria alternata (AA) was employed to evaluate the effects of genetic ablation of RAGE and pharmacological inhibition of the NLRP3 inflammasome on neutrophilic airway inflammation.ResultsAA exposure induced robust neutrophil-dominant airway inflammation and increased BALF levels of Th1/Th17 cytokines in wild-type mice, which was significantly reduced in RAGE-/- mice. Serum levels of IgE and IgG1 were increased similarly in both wild-type and RAGE-/- mice. Pharmacological inhibition of NLRP3 blocked the effects of AA exposure and NLRP3 inflammasome activation was RAGE-dependent. Neutrophil extracellular traps were elevated in the BALF of wild-type but not RAGE-/- mice and an atypical population of SiglecF+ neutrophils were identified in the BALF. Lastly, time-course studies found that RAGE expression promoted sustained neutrophil accumulation in the BALF of mice in response to AA.